Methodological problems of assessing industry average financial indicators (by the example of fertilizer producing companies) - O. V. Berezhnaya; A. V. Savtsova; N. V. Zelensky (Вестник Северо-Кавказского федерального университета)
Introduction. Methodological problems of assessing industry average financial ratios and indicators are solved in theoretical and applied sources in different ways, but most of these solutions have a number of significant shortcomings that are quite difficult to solve without developing new, specific tools and taking into account the statistical characteristics of companies of different groups.Goal. The purpose of the work is to study the methodological tools for assessing financial ratios at the macro- and mesolevel, to develop and test new approaches to their assessment using materials from fertilizer producing companies.Materials and methods. The information base was compiled by the financial statements of companies with the type of activity 20.15 - Production of fertilizers and nitrogen compounds for the period 2019 - 2022. The work took into account the features of institutional changes that occurred in open sources in 2022. The authors used deterministic modeling methods to assess the impact of companies that do not disclose their reports in 2022 in accordance with the Decree of the Government of the Russian Federation of March 12, 2022 No. 351; methods of financial analysis and modeling; statistical methods (weighted arithmetic mean, median, MAD - Median absolute deviation, outlier assessment based on interquartile ranges, grouping methods). The listed tools were used to assess the level, dynamics and factors of return on equity of companies in the industry; the features of the formation and dynamics of ROE in various typical groups are highlighted; An assessment of the homogeneity of groups according to the level of ROE and its factors was carried out.Results and discussion. Methodological approaches to estimating industry average values of financial ratios have been studied; The ROE of fertilizer producing companies was calculated on the basis of traditional methods, the disadvantages of its use were shown, and assessment tools using both traditional and robust indicators were proposed. The integrated use of various types of averages for companies in the industry as a whole and for their individual groups gives a more complete picture of the state and trends in the development of companies' financial policies.Conclusion. Conclusions are drawn about the level of profitability of fertilizer producing companies in an unstable economic environment; a conclusion is given on the development of tools for analyzing financial indicators at the industry level.